Conceptions of the women in a rural settlement concerning education in health - Sandra Beatris Diniz Ebling; Elza Maria Fonseca Falkemback; Vera Lúcia Oliveira Gomes; Marciele Moreira da Silva; Silvana de Oliveira Silva (Rev Rene)
his study aimed at understanding the conceptions of women in a rural settlement concerning education in health, focusing on the health of women, in the pursuit of apprehending matters of gender. This is a qualitative study of exploratory and descriptive type, made in a rural settlement of the Workers Without Land Movement in Southern Brazil. Data collection occurred from March to May 2011, through semi-structured interviews with nine women between 35 and 60 years of age residents in the settlement. The thematic analysis was used for the data. There is a multiplicity of opinions, beliefs, feelings, once the concepts of education in health of the settled workers are based on the value of more sensitive educational practices and their needs that transcend the reproductive dimension. Therefore, the peculiarities and diversities around the world of the settled workers must be considered in planning actions of health.